2017
DOI: 10.15761/hec.1000128
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Course on Patient Safety Management on the Patient Safety Competencies by Final Year Bachelor of Nursing Students in the Netherlands

Abstract: Background: Enhancing competencies of patient safety and quality of care is an actual and important issue in Bachelor of Nursing education. In 2010, the Dutch ministry of health adopted ten themes of patient safety and developed six competences for patient safe nursing care. Nursing schools integrated these competences in their Bachelor of nursing programs. This study evaluates the progress of undergraduate nursing students on the six competences, before and after a course on the management of innovation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Mansour et al [ 14 ] evaluated whether knowledge and attitudes about patient safety improved in a sample of 141 English nursing students after two master classes and facilitated group work, but the results of this pre-post-intervention study were not significant. Another study with 59 Dutch nursing students obtained satisfactory results after applying a structured program on patient safety, but the authors used an ad hoc questionnaire to globally assess the competencies established by the WHO and not the acquisition of knowledge, skills and attitudes [ 15 ]. Other authors also did not find significant differences in attitudes towards patient safety when they evaluated different educational interventions [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mansour et al [ 14 ] evaluated whether knowledge and attitudes about patient safety improved in a sample of 141 English nursing students after two master classes and facilitated group work, but the results of this pre-post-intervention study were not significant. Another study with 59 Dutch nursing students obtained satisfactory results after applying a structured program on patient safety, but the authors used an ad hoc questionnaire to globally assess the competencies established by the WHO and not the acquisition of knowledge, skills and attitudes [ 15 ]. Other authors also did not find significant differences in attitudes towards patient safety when they evaluated different educational interventions [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, different approaches can be found to improve the competencies in patient safety of nursing students. Some authors use traditional approaches with master classes [ 14 ] or structured courses [ 15 ]. Other authors introduce digital recordings in their courses [ 16 , 17 ] or use instructional methods such as the flipped classroom [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, there is a better development of knowledge, attitudes, values, skills and practices that make future professionals aware of promoting and improving the patient's safe care. [19][20] Research identified the use of different teaching methodologies, including several within the same CU. The coexistence of Education about patient safety Bohomol E traditional and innovative methodologies was clear, and there is no clear orientation of theoretical-methodological references that lead the teaching activity.…”
Section: Discussionmentioning
confidence: 99%
“…Karakteristik individu lainnya yaitu responden memiliki pendidikan terakhir diploma, belum pernah mengikuti pelatihan terkait patient safety. Olaf mengungkapkan bahwa ada perbedaan kompetensi patient safety yang signifikan antara sebelum dan sesudah dilakukan pelatihan terkait patient safety (14) .…”
Section: Pembahasan a Karakteristik Individuunclassified